Impacts of low oil price on China and the world natural gas industry chain - Yijun Liu; Li Ma (Natural Gas Industry B, 2016)
Since the second half of 2014, the crude oil price has been in rapid decline, which poses profound impacts on the global natural gas industry chain. The issue started to surface in the oil and gas sector on how to survive in such a situation. In this paper, an overview was first made on the world natural gas industry chain experiencing from the high-oil-price period to the low-oil-price period, then the influences of low oil price on natural gas production patterns, prices and development prospects, etc., and finally discussion focus was put on the challenges and opportunities brought about by the sustained low oil price to the natural gas industry chain in present China. The results are concluded as follows. First, under such low oil price situation, oil and gas companies at present have to cut capital expenditure to such a degree that the oil and gas output will be both of particular concern in the future. Second, low oil price will compel the falls of global natural gas prices to different degrees, so natural gas economy will drop greatly compared with crude oil prices. Third, such a low oil price will exert more severe impact on the high-cost unconventional natural gas sector; as a result, many unconventional oil and gas companies have suffered frequent bankruptcy at abroad, while such companies in China are holding different attitudes towards unconventional natural gas. Fourth, the oil and gas M&A market remains a laggard due to many other reasons. Fifth, this drop in oil prices is just occurring at the time when natural gas is developing so rapidly in China, which will bring both challenges and opportunities to the industrial structural reform of natural gas in China.